Investigation of the Frosting Performance and Improvement of the Defrosting Method for an Air-cooler under Low Temperature Condition - 刘恩海; 南晓红; 何媛 (Zhileng xuebao)
A theoretical analysis was carried out and a mathematical model was proposed for air - cooler frosting performance. The comparison of the calculated thickness Of the frost layer shows good agreement with the experimental data. The average difference is 8.99%. Further studies were carried out on the factors affecting heat transfer surface, the coefficient of heat transfer and the air side pressure drop during a frosting process. The characteristics of frost growth were analyzed under different inlet air temperature, relative humidity and velocity. The calculated results show that the inlet air temperature and the relative humidity of the inlet air have obvious influence on the frosting. Disadvantages of the present defrosting methods were analyzed. In order to reduce the first cost and energy consumption of the refrigeration system for a cold - storage enterprise, an improved method of defrosting for an ammonia air - cooler was proposed. It was proved that the improved method is practical for improving the energy saving, lowering manufacture cost and enhancing economical benefits.